Hubungan Kecemasan Matematika dan Motivasi Belajar dengan Prestasi Belajar Matematika Siswa - Apolonia Hendrice Ramda; Bedilius Gunur (JRPM (Jurnal Review Pembelajaran Matematika), 2021)
This study aimed to determine: (1) the relationship between mathematics anxiety and students' mathematics learning achievement; (2) the relationship between learning motivation and students' mathematics achievement; (3) the relationship between mathematics anxiety and learning motivation simultaneously with students' mathematics learning achievement. The population is all students of class VIII SMPN 7 Cibal, Manggarai Regency, East Nusa Tenggara totaling 108 students. Sampling was done by using a simple random sampling technique which was followed by a proportional random sampling technique. Data were obtained using questionnaires and tests. Data were analyzed using descriptive statistics, Pearson product-moment correlation, and multiple correlations. The results showed: (1) there is a negative relationship between mathematics anxiety and mathematics learning achievement; (2) there is a significant relationship between learning motivation and mathematics learning achievement; (3) there is a significant relationship between mathematics anxiety and learning motivation simultaneously with students' mathematics learning achievement.